Proliferation of human periodontal ligament mesenchymal cells on polished and plasma nitriding titanium surfaces - Rodrigo Alves Ribeiro; Rodrigo Gadelha Vasconcelos; Fernanda Ginani; José Sandro Pereira da Silva; Clodomiro Alves Júnior; Carlos Augusto Galvão Barboza (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the proliferative capacity of mesenchymal cells derived from human periodontal ligament on polished and plasma-treated titanium surfaces. Methods: Eighteen titanium disks were polished and half of them (n=9) were submitted to plasma nitriding using the cathodic cage technique. Mesenchymal cells were isolated from periodontal ligament of impacted third molars (n=2) and cultured on titanium disks (polished and nitrided) and on a plastic surface as a positive control of cell proliferation. Cell proliferation was analyzed and growth curves were constructed for the different groups by determining the number of cells adhered to the different surfaces at 24, 48 and 72 h after plating. Results: Higher cell number was observed for the nitrided surface at 24 and 48 h. However, no statistically significant difference in cell proliferation was observed between the two different surface treatments (p>0.05). Conclusions: We concluded that plasma nitriding produced surfaces that permitted the proliferation of human periodontal ligament mesenchymal cells. Associated to other physical and chemical properties, it is possible to assume the feasibility of plasma nitriding method and its positive effect on the early cellular events of osseointegration.